Before its time? : a case study and lessons of the Yasuní-ITT initiative - Dyar, Joel (Kansas State University, 2014)
This case study considers the lessons of Ecuador’s Yasuní-ITT initiative for future climate change policy and international conservation and development efforts. A comprehensive post-cancellation history of the initiative and background information regarding key domestic and international actors and institutions is presented in the Literature Review. Documents identified from LexisNexis and Google searches are analyzed to identify seven narratives of the initiative’s failure, which provide a basis for the suggestion of lessons. Questions regarding supply-side climate policy opportunities and challenges are explored. The initiative’s political mismanagement, design omissions and insufficient domestic political efforts, and a lack of contribution incentives are identified as the key causes of failure. The author concludes that the initiative’s supply-side model of shared sacrifices has the potential to align developed and developing country needs in support of greenhouse gas emissions reduction goals while addressing the difficulties posed by an emergent political economy of developing world resource extractivism in Ecuador and elsewhere. Future research regarding supply-side climate policies is suggested.
Keywords: Yasuni, Yasuni-ITT; Ecuador; United Nations Framework Convention on Climate Change; Supply side climate policy; Climate Change (0404); International Relations (0601); Public Policy and Social Welfare (0630)